Adaptación de lente progresivo en paciente femenino de 44 años de edad post operatorio de pterigión grado 3 que acude a Óptica Científica Guaranda, sucursal Montalvo. - Pazmiño Chichandi, Karla Jamilet (2025)
The present clinical case entitled “adaptation of progressive lenses in a 44 year old female patient after surgery for pterygium grade 3” in both eyes, due to the age of our patient already has presbyopia, this is a physiological eye condition associated with aging, ie the lens becomes less flexible and therefore will not focus properly on objects at close distances. Similarly, after performing all the relevant tests the patient also had myopia, this is because the eye is longer than normal and objects are not focused correctly on the retina but in front of it, making it difficult to see far away, likewise, I present an astigmatism which occurs because the cornea or lens have an abnormal shape, this will cause the light to curve differently when it enters the eye, astigmatism will cause the person to see blurred or distorted either in near or far vision. In this context, the adaptation to progressive lenses is presented as a viable solution, since the progressive lens has a graduation of the three distances, that is, in near vision, intermediate vision and distance vision, and also has a subtle transition in the different graduations.